A Decision-Support Model for Enhancing Innovative Business Performance: The Role of Technological Opportunism, Supervisory Support and Innovation Culture - Mohamed Alkashami; Umair Ahmed; Md. Lazim Mohd Zin; Ammar Ahmed (Decision Making: Applications in Management and Engineering, 2025)
This research examines the factors influencing innovative business performance by analysing how technological opportunism, supervisor support for innovation, innovation engagement, and organisational innovation culture affect managerial and organisational decision-making in innovation contexts. Employing a decision-analytic perspective and structural equation modelling using Smart PLS 3, quantitative data from the manufacturing industry were analysed. The findings indicate that technological opportunism impacts innovative business performance both directly and indirectly, highlighting the critical role of technology-related decision-making and adoption strategies. Additionally, the results demonstrate that supervisor support for innovation plays a crucial role in encouraging employees to participate in innovation activities, thereby enhancing overall innovation outcomes. The study also emphasises that an organisational culture promoting experimentation and inclusive decision-making cultivates an environment supportive of creativity and innovation. By combining insights from innovation management and decision sciences, the research suggests that effective innovation performance relies not solely on resource availability but on the quality of technological, supervisory, and cultural decision-making embedded within the organisation.